2010
DOI: 10.1016/j.atmosenv.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of self pollution from two diesel school buses using three independent methods

Abstract: We monitored two Seattle school buses to quantify the buses' self pollution using the dual tracers (DT), lead vehicle (LV), and chemical mass balance (CMB) methods. Each bus drove along a residential route simulating stops, with windows closed or open. Particulate matter (PM) and its constituents were monitored in the bus and from a LV. We collected source samples from the tailpipe and crankcase emissions using an on-board dilution tunnel. Concentrations of PM 1 , ultrafine particle counts, elemental and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…One important finding to date from micro-environmental monitoring suggests that kindergarten-aged children who play inside and outside their school in a high traffic area may be exposed to inhalatory PAH levels up to six times higher than what may occur in less polluted areas (Fiala et al, 2001). Also, school bus emissions may be large sources of children’s daily exposure to diesel and other combustion emissions such as PM 2.5 , and elemental carbon (Adar et al, 2008; Sally Liu et al, 2010). Residential monitoring can be conducted for much longer durations and remains another useful option for assessing PAH exposures, especially in young children.…”
Section: Introductionmentioning
confidence: 99%
“…One important finding to date from micro-environmental monitoring suggests that kindergarten-aged children who play inside and outside their school in a high traffic area may be exposed to inhalatory PAH levels up to six times higher than what may occur in less polluted areas (Fiala et al, 2001). Also, school bus emissions may be large sources of children’s daily exposure to diesel and other combustion emissions such as PM 2.5 , and elemental carbon (Adar et al, 2008; Sally Liu et al, 2010). Residential monitoring can be conducted for much longer durations and remains another useful option for assessing PAH exposures, especially in young children.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects were observed in very old and polluting buses with few emission controls, and it is uncertain whether they apply to the current diesel bus fleet. Studies of pre-MY 2007 school buses have suggested that self-pollution contributed an average of 7 to 8 μg/m 3 to in-cabin PM 2.5 concentrations ( 60 62 ), an exposure as large as current average ambient PM 2.5 levels in the United States (7.8 μg/m 3 ) ( 63 ). However, 80% of this PM 2.5 self-pollution was estimated to come from crankcase emissions ( 61 , 62 ), which were allowed to be released unfiltered until MY 2007 ( 64 – 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pre-MY 2007 school buses have suggested that self-pollution contributed an average of 7 to 8 μg/m 3 to in-cabin PM 2.5 concentrations ( 60 62 ), an exposure as large as current average ambient PM 2.5 levels in the United States (7.8 μg/m 3 ) ( 63 ). However, 80% of this PM 2.5 self-pollution was estimated to come from crankcase emissions ( 61 , 62 ), which were allowed to be released unfiltered until MY 2007 ( 64 – 66 ). Uncertainty remains about self-pollution in newer buses, as well as about the share of older buses in the current fleet that have been retrofitted.…”
Section: Discussionmentioning
confidence: 99%